Research progress on the role of oxidative stress in acute kidney injury - 邹晓彪; 罗助荣; 黄明方 (Linchuang shenzangbing zazhi)
Objective Acute kidney injury(AKI) is a multi-pathogenesis disease. Oxidative stress is a major factor in the pathogenesis of acute kidney injury and it can interact with other pathogenic factors to regulate the progression of acute kidney injury. This article reviewed the relationship between oxidative stress and other pathogenic factors, and the research progress on treatment of antioxidants for acute kidney injury.